Rôle des ganglions de la base dans le contrôle de la motricité : étude comportementale, électrophysiologique et neurochimique chez le rat sain et hémiparkinsonien - Abedi Mukutenga Pamphyle, Pamphyle (Université Mohammed V - Agdal, Faculté des Sciences, Rabat, 2013)
Parkinson’s disease is a neurodegenerative disease due to basal ganglia dysfunction and characterized by the degeneration of substantia nigra pars compacta dopaminergic neurons. In this way, this thesis account for the better understanding of the basal ganglia functional organization and the pathophysiology of Parkinson’s disease. Results obtained in this work showed that the dorsomedial striatum, an associative area of the dorsal striatum, play a critical role in the striatal motor control but not in the learning ability in rat. Moreover, dopamine depletion in the globus pallidus after intrapallidal injection of 6-OHDA induced major motor deficits in rats including a decrease of locomotor activity and contralateral paw use impairment, with changes in the neuronal activity of the subthalamic nucleus and substantia nigra pars reticulata. Furthermore, intrapallidal injection of agonists and antagonists of D1 and D2 dopamine receptors induced inhibition of locomotor activity in rats, while activation of the D1 and D2 receptors caused various changes in the neuronal activity of the STN and SNr. Results of our thesis underline the key role of the globus pallidus (GP) in the control of motor function by the basal ganglia, and show that dopamine innervation of the GP plays a major role in the modulation of basal ganglia nuclei activity and that dopamine depletion in this nucleus would play a role in the pathophysiology of Parkinson’s disease.
Keywords: Biologie; Neurosciences; Maladie de Parkinson; Striatum dorsomédian; Lésion électrolytique; Dopamine; 6-hydroxydopamine; Globus pallidus; Noyau sous-thalamique; Substance noire pars reticulata; Activité locomotrice; Electrophysiologie